A large spin-crossover [Fe4L4]8+ tetrahedral cage12. Issue 30 (14th August 2015) - Li, Li; Saigo, Naoto; Zhang, Yingjie; Fanna, Daniel J.; Shepherd, Nicholas D.; Clegg, Jack K.; Zheng, Rongkun; Hayami, Shinya; Lindoy, Leonard F.; Aldrich-Wright, Janice R.; Li, Chun-Guang; Reynolds, Jason K.; et al.
<x xml:space="preserve">Abstract</x> A large iron(ii) tetrahedral cage displays temperature induced spin-crossover and liesst effects.